Evidence-Based Medicine in Otolaryngology Part 10: Cost-Effectiveness Analyses in Otolaryngology. (September 2019) - Caulley, Lisa; Rodin, Danielle; Kilty, Shaun; Randolph, Gregory; Hunink, Myriam G.; Shin, Jennifer J.
Clinicians seek to pursue the most clinically effective treatment strategies, but costs have also become a key determinant in contemporary health care. Economic analyses have thus emerged as a valuable resource to both quantify and qualify the value of existing and emerging interventions and programs. Cost-effectiveness analyses estimate the benefits gained per monetary unit, providing insights to guide resource allocation. Herein, we delineate the related concepts and considerations to facilitate understanding and appraisal of these analyses, so as to better inform the stakeholders in our otolaryngology community.